Factors Of Psychological Adaptation Freshmen Students - Alisher Komiljonovich Sanayev; Pavel Nikolayevich Ustin; Komiljon Buribaevich Murotmusaev (Genius Journals, 2022)
The article highlights the mechanisms and principles of the theory of psychological adaptation of a personality. The classification of personality needs and motives, adaptive complexes as well as objective and subjective factors influencing the formation of personality are considered. Adaptation of students in the context of personality psychologization is considered as a process that allows a person to take his place in society and be professionally realized in it. The student's maladaptation is characterized by undifferentiated goals and types of activities, narrowing of the range of his communication and problems to be solved, as well as the rejection of norms and values of the new social environment, which is the higher education institution
Keywords: Psychology; adaptation; psychological factor; adaptive complex